ANALISIS PENGUATAN PROFIL PELAJAR PANCASILA PADA DIMENSI BERKEBINEKAAN GLOBAL BERBASIS PROYEK KEARIFAN LOKAL DI SEKOLAH DASAR - Ratna; Sutisna, Atang; Nurfirdaus, Nunu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Strengthening the global dimension in the formation of the Pancasila student profile at school is important to recognize and appreciate cultural diversity as an effort to maintain the country's identity. The purpose of this study is to explain how SD Negeri Gereba has strengthened the dimensions of global citizenship through local wisdom projects for fourth grade students at SD Negeri Gereba. This research uses a qualitative method with a case study research design. Data collection techniques in this study used observation, interviews, questionnaires, and documentation. Data analysis techniques using the Milen and Huberman model include data reduction, data display, and conclusion drawing (Verification). The results of this study indicate that in the design of project activities have not been fully in accordance with the guidelines for the implementation of the Pancasila project (P5), SD Negeri Gereba does not yet have a school-specific P5 module. At the implementation stage, SD Negeri Gereba chose a local wisdom project with traditional food project activities and the results were displayed at the market day activity at the work title event held by the school. This project is expected to strengthen the dimensions of global diversity, namely students can recognize the cultures that exist in Indonesia, the creation of good cooperation behavior between students, mutual respect and tolerance between cultural differences.